Analisis Kelayakan Investasi Sistem PLTS Atap pada Gedung Lecture Building Universitas Udayana - Yoga, Ida Bagus Savitar Dharma; Sukerayasa, I Wayan; Setiawan, I Nyoman; Janardana, I Gusti Ngurah; Budiastra, I Nyoman; Suartika, I Made (Innovative: Journal Of Social Science Research, 2025)
The use of renewable energy, especially Solar Power Plants (PLTS) is an alternative solution in facing increasing electricity needs and limited conventional energy supply. The Udayana University Lecture Building, which has a high level of operation during the day, is the object of designing a rooftop solar power plant system with an on-grid configuration equipped with a Battery Energy Storage System (BESS). This study aims to evaluate the feasibility of investing in the solar PV system to be designed. The analysis methods used include the calculation of Life Cycle Cost (LCC), Cost of Energy (CoE), Capital Recovery Factor (CRF), Net Present Value (NPV), Internal Rate of Return (IRR), Discounted Payback Period (DPP), and Profitability Index (PI). The results of the investment feasibility analysis showed that the initial investment of IDR 1,298,931,811 resulted in an NPV value of IDR 123,306,233, IRR of 21.01%, DPP for 21.9 years, and PI of 1.09. Thus, this project was declared financially feasible to be implemented.